2012
DOI: 10.1158/1078-0432.ccr-11-2711
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Hypoxia Predicts Biochemical Failure following Radiotherapy for Clinically Localized Prostate Cancer

Abstract: Purpose: Tumor hypoxia is an important determinant of outcome in many human malignancies and is associated with treatment resistance and metastases. The aim of this study was to determine the effect of hypoxia in patients with prostate cancer treated with radiotherapy.Experimental Design: Tumor hypoxia was measured in 247 patients with clinically localized prostate cancer before radiotherapy, with or without hormonal therapy. The median pO 2 was 6.8 mm Hg and the median hypoxic percentage less than 10 mm Hg (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
205
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 237 publications
(211 citation statements)
references
References 31 publications
4
205
1
1
Order By: Relevance
“…The proportional hazards assumption was checked for each variable by looking at the Schoenfeld residuals. As the proportional hazards assumption was found to be violated for metformin use, a Cox regression model was used to model metformin as a time-varying coefficient, adjusting for clinical T-category (T1 vs. T2þ), Gleason score (6 vs. 7 vs. 8þ), pretreatment PSA (continuous), and the use of hormonal treatment (Y vs. N) as previously described (2). All analyses were done using SAS version 9.2 and R version 2.12.1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportional hazards assumption was checked for each variable by looking at the Schoenfeld residuals. As the proportional hazards assumption was found to be violated for metformin use, a Cox regression model was used to model metformin as a time-varying coefficient, adjusting for clinical T-category (T1 vs. T2þ), Gleason score (6 vs. 7 vs. 8þ), pretreatment PSA (continuous), and the use of hormonal treatment (Y vs. N) as previously described (2). All analyses were done using SAS version 9.2 and R version 2.12.1.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of tumor hypoxia is a negative prognostic factor in tumors treated with curative intent by radiotherapy across multiple sites, including squamous cell carcinoma of the head and neck (1) and prostate carcinoma (2). Tumor cells located further than approximately 150mm from vessels experience "diffusion-limited" hypoxia as oxygen is consumed by the tumor cells more proximal to the vessels (3).…”
Section: Introductionmentioning
confidence: 99%
“…24,27,87 Estimation of oxygenation in the prostate provides an additional problem, since the tumour often infiltrates throughout the gland, which may affect measurement of "normal" oxygen levels. It has been reported that the "normal" tissue is not significantly different in oxygen level from tumours; 26,88 however, it is possible that the normal tissue is influenced by the presence of tumour. In one study, the normal prostate was assessed in two patients prior to surgery for bladder cancer and they showed a mean of 3.4% oxygen (26.2 mmHg).…”
Section: The Importance Of Tumour Hypoxia On Survival Outcomes Followmentioning
confidence: 95%
“…Median p02 was 6.8 mm Hg and the median percentage of hypoxia was less than 10 mm Hg [47]. Their findings show that hypoxia is associated with early biochemical recurrence and local recurrence in prostate after radiotherapy or radiotherapy associated with hormone therapy.…”
Section: Hypoxia In Prostate Cancermentioning
confidence: 87%